Effect of mixed meal replacement of soybean meal on growth performance, nutrient apparent digestibility, and gut microbiota of finishing pigs - Zhentao He; Shuai Liu; Xiaolu Wen; Shuting Cao; Xianliang Zhan; Lei Hou; Yaojie Li; Shaozhen Chen; Huayu Zheng; Dongyan Deng; Kaiguo Gao; Xuefen Yang; et al. (Frontiers in Veterinary Science, 2024)
IntroductionThis study was carried out to investigate the effects of mixed meal (rapeseed meal, cotton meal, and sunflower meal) replacement soybean meal on growth performance, nutrient apparent digestibility, serum inflammatory factors and immunoglobulins, serum biochemical parameters, intestinal permeability, short-chain fatty acid content, and gut microbiota of finishing pigs.MethodsA total of 54 pigs with an average initial weight of 97.60 ± 0.30 kg were selected and randomly divided into 3 groups according to their initial weight, with 6 replicates in each group and 3 pigs in each replicate. The trial period was 26 days. The groups were as follows: control group (CON), fed corn-soybean meal type basal diet; Corn-soybean-mixed meal group (CSM), fed corn-soybean meal-mixed meal diet with a ratio of rapeseed meal, cotton meal, and sunflower meal of 1:1:1 to replace 9.06% soybean meal in the basal diet; Corn-mixed meal group (CMM), fed a corn-mixed meal diet with a ratio of Rapeseed meal, Cotton meal and Sunflower meal of 1:1:1 to replace soybean meal in the basal diet completely. The crude protein level of the three diets was maintained at 12.5%.ResultsOur findings revealed no significant impact of replacing soybean meal with the mixed meal (rapeseed meal, cotton meal, and sunflower meal) on the ADG (Average daily gain), ADFI (Average daily feed intake), and F/G (Feed gain ratio) (P > 0.05), or crude protein, crude fat, and gross energy (P > 0.05) in the diet of finishing pigs. Compared with the CON group, the serum interleukin 6 (IL-6) and interleukin 10 (IL-10) concentrations were significantly decreased in the CMM group (P < 0.05). However, there is no significant effect of the mixed meal (rapeseed meal, cotton meal, and sunflower meal) replacing soybean meal in the diet on the serum interleukin 1β (IL-1β), interleukin 8 (IL-8), tumor necrosis factor-alpha (TNF-α), immunoglobulin A (IgA), immunoglobulin G (IgG), and immunoglobulin M (IgM) concentrations (P > 0.05). Concordantly, there is no significant effect of mixed meal (rapeseed meal, cotton meal, and sunflower meal) replacing soybean meal in the diet on the serum antioxidant capacity, such as total antioxidant capacity (T-AOC), catalase (CAT), and malondialdehyde (MDA) levels of finishing pigs. Moreover, compared with the CON group, serum low-density lipoprotein (LDL-C) levels were significantly lower in the CSM group (P < 0.05) and their total bilirubin (TBIL) levels were significantly lower in the CMM group (P < 0.05). There is not a significant effect on serum D-lactate and diamine oxidase (DAO) concentrations (P > 0.05). The next section of the survey showed that the replacement of soybean meal with a mixed meal (rapeseed meal, cotton meal, and sunflower meal) in the diet did not significantly influence the acetic acid, propionic acid, butyric acid, valeric acid, isobutyric acid, and isovaleric acid in the colon contents (P > 0.05). Furthermore, compared with the CON group, the CMM group diet significantly increased the abundance of Actinobacteria at the phylum level (P < 0.05), U_Actinobacteria at the class level (P < 0.05), and U_Bacteria at the class level (P < 0.05). The result also showed that the CMM group significantly reduced the abundance of Oscillospirales at the order level (P < 0.05) and Streptococcaceae at the family level (P < 0.05) compared with the CON group. The Spearman correlation analysis depicted a statistically significant positive correlation identified at the class level between the relative abundance of U_Bacteria and the serum T. BILI concentrations (P < 0.05). Moreover, a significant negative correlation was detected at the order level between the relative abundance of Oscillospirales and the levels of acetic and propionic acids in the colonic contents (P < 0.05). Additionally, there was a significant positive correlation between the serum concentrations of IL-6 and IL-10 and the relative abundance of the family Streptococcaceae (P < 0.05).DiscussionThis study demonstrated that the mixed meal (rapeseed meal, cotton meal, and sunflower meal) as a substitute for soybean meal in the diet had no significant negative effects on the growth performance, nutrient apparent digestibility, serum immunoglobulins, serum antioxidant capacity, intestinal permeability, short-chain fatty acid content, and diversity of gut microbiota of finishing pigs. These results can help develop further mixed meals (rapeseed meal, cotton meal, and sunflower meal) as a functional alternative feed ingredient for soybean meals in pig diets.